REPORT OF A RARE CASE OF TYPE I NEUROFIBROMATOSIS IN A FEMALE PATIENT IN RIYADH, SAUDI ARABIA. - Fatima Yahya ALBishry1, Hadeel Saad2, Nawaf Alotaibi3, Fahad Alnafisah4, Al Hanouf Al Assiri5, (Chelonian Research Foundation, 2024)
Neurofibromatosis type 1 (NF-1), which is sometimes called von Recklinghausen's disease, is a rare genetic trait that causes many neurofibromas to form on the skin and nerves. These are harmless lumps. Most neurofibromas in the head and neck are found in soft tissues. We talk about a case of NF-1 in a 53-year-old Saudi woman in this report. During childhood, numerous darkly pigmented macules appeared on the epidermis, indicating the onset of the disease. The patient had pervasive freckling and café au lait spots on her body, as well as a diffuse, approximately 4 cm 3 cm swelling. Notably, large masses extending from her left ear to her left orbit were observed on her visage. These aggregates were distinct, painless, and mobile. On the margins, dorsum, and central border of the tongue, there were numerous exophytic lesions.The patient's diagnosis of NF-1 was confirmed based on the fulfillment of two or more diagnostic criteria established by the National Institute of Health Consensus Development Conference. Following a thorough surgical ablation, no recurrence was detected during the 15-month follow-up period. Key Words: Neurofibromatosis 1, Soft tissue, Neurofibromas, Case report.